Maximizing Religious Capital: Building English Villages Based on Islamic Education around the Campus - Muhammad Saifullah; Sofa Muthohar; Sayyidatul Fadlilah (FITK UIN Walisongo, 2019)
Some Islamic groups, especially the traditional Indonesian circles, have a negative view of English. English is considered the language of infidel invaders and the language of hell. This paper aims to describe the development of society in implementing Islamic religious education while eliminating the negative impression of the use of English in Islamic societies to be an important language to be learned as a language of global communication. The research method uses the sociological phenomenological method. The results showed that the Amanah village had six social capital namely human capital, social capital, natural capital, physical capital, and financial capital and religious capital. The development strategy undertaken is to maximize religious capital by establishing religious institutions and carrying out religious activities by being given English language lessons. There are two centers of activity, namely the Baitussalam mosque and the AleC (Amanah Learning Center). Other capital that plays a significant role is social capital that is inclusive and accommodating towards migrants.AbstrakSebagian masyarat Islam terutama kalangan tradisional Indonesia berpandangan negative terhadap bahasa Inggris. Bahsa inggris dianggap sebagai bahasa para penjajah yang kafir dan bahasa neraka. Tulisan ini bertujuan untuk menggambarkan pembangunan masyarakat dalam melaksanakan pendidikan Agama Islam sekaligus menghilangkan kesan negative penggunaan bahasa Inggris di masyarakat Islam menjadi bahasa penting untuk dipelajari sebagai bahasa komunikasi global. Metode penelitian menggunakan metode fenomenologis sosiologis. Hasil penelitian menunjukkan bahwa kampung Amanah memiliki enam modal sosial yaitu human capital, social capital, natural capital, physical capital dan financial capital serta religious capital. Strategi pembangunan yang dilakukan yaitu dengan memaksimalkan modal relgius dengan mendirikan institusi agama dan menjalankan kegiatan-kegiatan agama dengan diberi sisipan pelajaran bahasa Inggris. Pusat kegiatan ada dua yaitu masjid baitussalam dan AleC (Amanah Learning Center). Modal lain yang sangat berperan adalah modal sosial masyarakat yang bersikap inklusif dan akomodatif terhadap para pendatang.